Computational modelling and experimental tank testing of the multi float WaveSub under regular wave forcing. (June 2020) - Faraggiana, E.; Whitlam, C.; Chapman, J.; Hillis, A.; Roesner, J.; Hann, M.; Greaves, D.; Yu, Y.-H.; Ruehl, K.; Masters, I.; Foster, G.; Stockman, G.
Abstract: A submerged wave device generates energy from the relative motion of floating bodies. In WaveSub, three floats are joined to a reactor; each connected to a spring and generator. Electricity generated damps the orbital movements of the floats. The forces are non-linear and each float interacts with the others. Tuning to the wave climate is achieved by changing the line lengths, so there is a need to understand the performance trade-offs for a large number of configurations. This requires an efficient, large displacement, multidirectional, multi-body numerical scheme. Results from a 1/25 scale wave basin experiment are described. Here, we show that a time domain linear potential flow formulation (Nemoh, WEC-Sim) can match the tank testing provided that suitably tuned drag coefficients are employed. Inviscid linear potential models can match some wave device experiments; however, additional viscous terms generally provide better accuracy. Scale experiments are also prone to mechanical friction, and we estimate friction terms to improve the correlation further. The resulting error in mean power between numerical and physical models is approximately 10%. Predicted device movement shows a good match. Overall, drag terms in time domain wave energy modelling will improve simulation accuracy in wave renewable energy device design. Highlights: Multi body wave device in heave and surge performance under regular wave forcing. Compares computational modelling and experimental tank testing. Linear potential flow model improved by inclusion of drag terms. Investigate relationship between drag coefficient and Keulegan-Carpenter number. Shows how mechanical friction influences the device motion.